2007
DOI: 10.1007/s00440-007-0078-x
|View full text |Cite
|
Sign up to set email alerts
|

Large deviations estimates for self-intersection local times for simple random walk in $${\mathbb{Z}}^3$$

Abstract: We obtain large deviations estimates for the self-intersection local times for a simple random walk in dimension 3. Also, we show that the main contribution to making the self-intersection large, in a time period of length n, comes from sites visited less than some power of log(n). This is opposite to the situation in dimensions larger or equal to 5. Finally, we present an application of our estimates to moderate deviations for random walk in random sceneries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…Remark 1.7 Recently, the first author has obtained in [1] large deviations estimates for the SILT in d = 3, and has shown that the main contribution in making the SILT large, in a time period of length n, comes from sites whose local times is less than some power of log(n). Also, a diagram for the ζ -exponent for the deviations for RWRS is given in d = 3.…”
Section: Proposition 16mentioning
confidence: 99%
See 3 more Smart Citations
“…Remark 1.7 Recently, the first author has obtained in [1] large deviations estimates for the SILT in d = 3, and has shown that the main contribution in making the SILT large, in a time period of length n, comes from sites whose local times is less than some power of log(n). Also, a diagram for the ζ -exponent for the deviations for RWRS is given in d = 3.…”
Section: Proposition 16mentioning
confidence: 99%
“…About R 1 We first obtain the existence of some exponential moments for J (l) . For each l ≤ l * , k = 1, .…”
Section: Proofmentioning
confidence: 99%
See 2 more Smart Citations
“…Eξ(0) = 0, with variance σ 2 > 0, and satisfies E|ξ(0)| 3 < ∞ and Cramér's condition, E e θξ(0) < ∞ for some θ > 0. (1) We are interested in the cumulative sceneries as seen by the random walker,…”
Section: Introductionmentioning
confidence: 99%